A quinta, a capela e o portal: análise do potencial de uma paisagem histórica inserida no conjunto arquitetônico da cidade de São Luís do Maranhão - Alcântara, Ariadne Ketini Costa de (CEM – Cultura, Espaço & Memória, 2021)
Quinta das Laranjeiras, owned by the merchant and military José Gonçalves da Silva, is part of the landscape of the outskirts of the city of São Luís do Maranhão from the time of its construction, in 1789, until the present day. Located at the end of the old Caminho Grande, now Oswaldo Cruz street, the Quinta has a private chapel and an imposing portal decorated with lioz stones, which reproduces the coat of arms of the Portuguese merchant. Functioning as landmarks of the boundaries of this site, these architectural elements remained during the 19th and 20th centuries as a reference for the urban evolution of São Luís, even after the various stages of the uncharacterization of the Quinta and its surroundings. In this sense, this article intends to discuss the concept of historical urban landscape attributing to Quinta das Laranjeiras the necessary patrimonial potential for a case study that understands the derivations of this category. Using UNESCO and IPHAN definitions of cultural landscape as parameters, we will analyze the formation of a stratification of meanings that have been accumulated through the historical and economic processes, in addition to punctuating the effects of the toppling of Quinta das Laranjeiras